Promoting Green Growth through Water Resources Management : The Case of Republic of Korea - Ishiwatari, Mikio; Wataya, Eiko; Shin, Taesun; Kim, Daeil; Song, Jiseon; Kim, Seyi (2016)
Water security and water quality affect numerous economic sectors and areas: agriculture, energy, disaster management, and others. Countries need balanced and integrated approaches that are economically, environmentally, and socially sustainable. Threats related to climate change have added to the complexity, and to the importance, of water resource management. Korea’s integrated water resources management approach since the 1990s reflects the country’s “green” climate-resilient development path. The Korean Green Growth Trust Fund’s (KGGTF) 3rd “Knowledge Note”, Promoting Green Growth through Water Resources Management: the Case of Republic of Korea, outlines key responses to Korea’s water resource challenges. The report highlights the Korean Government’s “Four Major River Restoration Project (4MRRP)”, a multi-purpose, green-growth infrastructure initiative. Involving five ministries and 78 local authorities in a comprehensive and integrated approach, the Note showcases lessons from 4MRRP for other countries to learn from Korea’s experience overcoming institutional, legislative, governance, technical and financial hurdles.